2022
DOI: 10.3390/vaccines10081166
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Vaccine Booster Dose Willingness among Patients with Inflammatory Bowel Disease on Infliximab and Vedolizumab: A Cross-Sectional Study

Abstract: Background: Vaccination has been effective in preventing COVID-19 infections and related mortality. However, waning immunity after two-dose vaccination prompted health authorities to recommend a third dose of COVID-19 vaccine to boost immunity. The aim of our study was to assess willingness to receive a third (booster) dose among patients with inflammatory bowel disease (IBD). Methods: A cross-sectional study was performed at an IBD tertiary care center. Patients were recruited at the infusion room from 1 Janu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
0
2
1
Order By: Relevance
“…A recent study survey from China among 350 CKD patients showed that around 70.29% of the respondents reported their willingness to receive a COVID-19 booster vaccine dose [ 19 ]. When compared to a recent study conducted among patients with another chronic medical condition (inflammatory bowel disease) in Kuwait that reported only 58.1% acceptance, the willingness to receive a COVID-19 vaccination booster dose was higher in our study [ 22 ]. Another study among healthcare workers in SA found that 71.1% of study participants reported positive intent for receiving a COVID-19 booster dose, which is lower than in our study [ 20 ].…”
Section: Discussioncontrasting
confidence: 78%
“…A recent study survey from China among 350 CKD patients showed that around 70.29% of the respondents reported their willingness to receive a COVID-19 booster vaccine dose [ 19 ]. When compared to a recent study conducted among patients with another chronic medical condition (inflammatory bowel disease) in Kuwait that reported only 58.1% acceptance, the willingness to receive a COVID-19 vaccination booster dose was higher in our study [ 22 ]. Another study among healthcare workers in SA found that 71.1% of study participants reported positive intent for receiving a COVID-19 booster dose, which is lower than in our study [ 20 ].…”
Section: Discussioncontrasting
confidence: 78%
“…However, another investigation showed that booster hesitancy was higher among those who received Pfizer vaccines [ 5 ]. Seboka et al [ 13 ] and Shehab et al [ 46 ] found higher booster hesitancy among people receiving the AstraZeneca vaccine. On the contrary, Al-Qerem et al [ 29 ] reported lower booster hesitancy among AstraZeneca recipients.…”
Section: Resultsmentioning
confidence: 99%
“…In line with our findings, other studies have also identified specific factors influencing COVID-19 vaccination rates in IBD patients. Female patients, those above the age of 50, and expatriates were more likely to receive COVID-19 vaccines [46,47]. Similarly, a study by Kwon et al observed higher vaccination uptake among IBD patients who were on biologics and of white or Asian race.…”
Section: Discussionmentioning
confidence: 91%